COMPUTER MODELING OF CHITOSAN ADSORPTION ON A CARBON NANOTUBE - J.T. Azimov; J.T.Azimov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Molecular Dynamics (MD) simulation results for the adsorption process of chitosan oligomer on a carbon nanotube (CNT) are presented. Ab initio DFT calculations are employed to obtain optimal geometric parameters and atomic charge distribution of the chitosan monomer and dimer. Then by means of classic molecular dynamics the binding energy of a chitosan molecule with CNT calculated. It is found that character of the interaction between a chitosan molecule and CNT is non-specific.